Approaches to Enhance Game-Based Teaching Literacy for Kindergarten Major Students - GUO, PU (Pacific International Journal, 2024)
This study examines the significance of early literacy development in kindergarten students and explores the effectiveness of game-based teaching as a means to enhance literacy instruction. Game-based teaching, characterized by interactive and playful activities, has gained prominence, especially with the advent of digital games and educational apps. The research provides a historical and theoretical backdrop, recognizing the challenges and advantages of this approach, and delves into strategies for its successful implementation, emphasizing the pivotal role of educators. The study also highlights the potential for collaboration, independent learning, and the transference of skills acquired through gaming to real-world contexts. While acknowledging challenges such as technological access and teacher training, it offers strategies to overcome them, and underscores the need for adaptations to align with the unique needs of kindergarten students. This research underscores the role of game-based teaching in fostering early literacy skills, setting the stage for students’ academic journeys.